The decision to purchase genome edited food products by Iranian consumers: theory of planned behavior as a social intervention tool - Valizadeh, Naser; Karami, Shobeir (Frontiers in Genome Editing, 2025)
The main aim of present study was to analyze the consumers’ preferences about genome/gene-edited food products in Iran. For this purpose, an extended version of the theory of planned behavior was used as a social intervention tool. The theory of planned behavior was firstly extended using the introduction and new variable of trust in gene-edited products and perceived benefits of gene-edited food products, but in the next step, it was also analyzed statistically. To achieve the main objective of the research, a representative sample was selected from the population of purchasers of gene-edited products, and data were collected using a cross-sectional survey. The validity and reliability of the data collection tool was evaluated and confirmed using different quantitative and qualitative methods in the pilot stages and after the main survey. The results of structural equation modeling showed that the attitude towards gene-edited food products, perceived behavioral control, and the subjective norms of gene-edited products had positive and significant effects on the intention to purchase these products. The results of the study indicated that two newly introduced variables to the theory of planned behavior, namely, trust in gene-edited products and the perceived benefits of gene-edited products also had positive and significant effects on the intention to purchase these products. Based on the results, the framework employed and extended in this study can provide the basis for effective interventions to improve consumers’ preference for gene-edited food products. Also, some practical suggestions were provided for policymakers, managers, and producers of these products.